Ethics at the end of life. (October 2016) - Baker, Idris
Abstract: End-of-life care has always been prominent in discussions of clinical ethics. Almost 30% of hospital inpatients are in their last year of life. Doctors frequently encounter people with end-of-life care needs and should to be equipped to respond. The bewildering array of what has been written about it leaves many doctors, other healthcare workers and the public uncertain and confused. What key things should doctors know and understand? The principles are the same as in any area of medicine, but they have to be applied in a different context. Some goals (e.g. long-term survival) can no longer be achieved, but new ones (e.g. new ways to improve quality of life) become available. By clearly understanding the ethics, we can learn how to do good end-of-life care. This article briefly addresses key areas including why ethics matters in end-of-life care, how to apply familiar principles, how we can respond to some barriers to respect for autonomy, applying the doctrine of double effect and understanding the application of ethics in the last days of life. It also gives pointers to further detailed reading.